Optimization of guanosine-based hydrogels with boric acid derivatives for enhanced long-term stability and cell survival - Merino-Gómez, Maria; Godoy-Gallardo, Maria; Wendner, Mathias; Mateos-Timoneda, Miguel A.; Gil, F. Javier; Perez, Roman A. (Frontiers in Bioengineering and Biotechnology, 2023)
Tissue defects can lead to serious health problems and often require grafts or transplants to repair damaged soft tissues. However, these procedures can be complex and may not always be feasible due to a lack of available tissue. Hydrogels have shown potential as a replacement for tissue grafts due to their ability to support cell survival and encapsulate biomolecules such as growth factors. In particular, guanosine-based hydrogels have been explored as a potential solution, but they often exhibit limited stability which hampers their use in the biofabrication of complex grafts. To address this issue, we explored the use of borate ester chemistry and more complex boric acid derivatives to improve the stability and properties of guanosine-based hydrogels. We hypothesized that the aromatic rings in these derivatives would enhance the stability and printability of the hydrogels through added π-π stack interactions. After optimization, 13 compositions containing either 2-naphthylboronic acid or boric acid were selected. Morphology studies shows a well-defined nanofibrilar structure with good printable properties (thixotropic behaviour, print fidelity and printability). Moreover, the pH of all tested hydrogels was within the range suitable for cell viability (7.4-8.3). Nevertheless, only the boric acid-based formulations were stable for at least 7 days. Thus, our results clearly demonstrated that the presence of additional aromatic rings did actually impair the hydrogel properties. We speculate that this is due to steric hindrance caused by adjacent groups, which disrupt the correct orientation of the aromatic groups required for effective π-π stack interactions of the guanosine building block. Despite this drawback, the developed guanosine-boric acid hydrogel exhibited good thixotropic properties and was able to support cell survival, proliferation, and migration. For instance, SaOS-2 cells planted on these printed structures readily migrated into the hydrogel and showed ~100 cell viability after 7 days. In conclusion, our findings highlight the potential of guanosine-boric acid hydrogels as tissue engineering scaffolds that can be readily enhanced with living cells and bioactive molecules. Thus, our work represents a significant advancement towards the development of functionalized guanosine-based hydrogels.